PRODUKTIVITAS PASTURA ALAM PADA MUSIM HUJAN DI KECAMATAN NEKAMESE KABUPATEN KUPANG - Bernadete Barek Koten; Ati Maria Kase; Redempta Wea; Melkianus Dedimus Same Randu (Partner, 2022)
The present study aims to evaluate fresh and dry matter production, botanical composition, and carrying capacity of natural pasture during the rainy season in Oemasi Village, Nekamese District, Kupang Regency, East Nusa Tenggara Province. The fresh and dry matter production was evaluated using the Halls method. The botanical composition was analyzed using the dry weight rank method, and the carrying capacity was calculated using the Voisin formula. The data obtained were descriptively analyzed. The results showed that the average production of fresh and dried materials was respectively 1.64 tons/ha and 0.90 tons/ha. The botanical composition comprises 61.70% grass, 9.68% legumes, and 28.62% weeds. The carrying capacity of natural pasture is 0.84 UT/ha. The findings of the present study suggest that the carrying could be increased by introducing the creeping of legume vines and minimizing non-palatable weed species.Keywords: Botanical composition, Carrying Capacity, Fresh and dry production.